Em defesa da sociedade: práticas de tutela à menoridade na Fortaleza Belle Époque - Muniz Neto, João Silveira (2014)
This research discusses the guardianship directed at minors in Belle Époque Fortaleza city (last decades of the 1800’s and first decades of the 1900’s). From Michel Foucault’s (1926-1984) genealogical perspective, are discussed discursive and non-discursive practices that allowed the emergence of speeches in favour of poor childhood support in this city. In this period, countless speeches (stemming from the legal, medical, pedagogical, and psychological areas, among others) which self-arrogated the title of "scientific", guided and produced a close association between poverty and danger. The imminence of danger contained in atavistic heritage of grassroots classes reverberated in the treatment to the poor children. In a Fortaleza city passing through a modernization and installation of economic liberalism, the poor childhood – conceived from the dimension of future – represented an obstacle to progress, since it was forged as the anti-model of the modern citizen: resourceless, illiterate, ignorant of ideals of aseptic hygiene, unable to raise the nationality without receiving assistance. Since then, the guardianship of minors becomes one of the strategies of biopolitical governmentality to guarantee the metropolis modernization. As scope of analysis, it is used the official discourse (messages by the presidents of the Province and State of Ceará sent to the legislature), print media (epoch’s newspapers: Correio do Ceará; Jornal do Ceará; O Nordeste), and academic discourse (doctoral theses of the Ceará Faculty of Law between 1920 and 1930). To access such sources, we visited some research establishments, such as the Anthropological Historical and Geographical Institute of Ceará, the Public Archives of the State of Ceará and Menezes Pimentel Public Library, all located in the city of Fortaleza. From the analysis of the sources, it was noted that occured two major shifts in protecting the juvenile segment in the researched space-time: 1. The displacement of the charitable-religious paradigm for the philanthropic-hygienic paradigm in actions of governmentality to the poor population in general; 2. The second shift is rather an extension of government strategies that fall on the "subject of child assistance": before the drought of 1877-79 the child that was able to receive help from charities was the orphan child (conceived as "a pitty little one" and helpless); at the turn of the nineteenth and twentieth centuries the childhood that requires governance on itself in Fortaleza is a poor childhood – which happens to be taken as potentially delinquent – larger group that includes the first one. The event secas, moreover, with its frequent intervals and its fatal and catastrophic consequences for the territory and economy of Ceará, also have major importance within childhood’s strategies of governance thought in this city which was wanted to be modern between nineteenth and twentieth centuries.